Connecting the dots: a qualitative study of dog-bite data in Calgary (AB, Canada) - Mouton, Morgan; Rault, Dawn; Rock, Melanie (International Journal of Population Data Science, 2018)
Introduction Worldwide, dog-bites remain a leading cause of pediatric injuries. Local governments are key because they can enact and enforce policies on dogs. The City of Calgary has earned an international reputation for its approach to regulating dogs and dog-owners, which has resulted in marked reductions in per capita dog-aggression complaints. Objectives and Approach This presentation reflects on how data on dogs are collected, sorted and used by local governments. Our approach has been qualitative in nature: we observed bylaw officers during ride-alongs, and we conducted in-depth interviews with officials who conceived and/or use the databases involving dogs in Calgary. We took a particular interest in the migration of the City of Calgary’s ‘canine data’ (e.g., dog licensing, reports by enforcement officers) to a more comprehensive database listing all of the incidents recorded by municipal services (including ‘911’ and ‘311’ calls, etc.). Results Preliminary results point to difficulties in linking data stemming from several sources. Within the municipality itself, the transition comes with important challenges. Moreover, to improve public health surveillance for dog-bites, and ultimately to improve preventive strategies, other sources of data should be linked, including emergency services, animal welfare charities, and and veterinary clinics. This fragmentation of available data would be difficult to overcome. Local governments and animal welfare charities may cooperate during investigations but do not share their administrative data. The issue of privacy is a strong barrier for municipal services to obtain healthcare data, while veterinary clinics are private entities that have few incentives to align with administrative data held by local governments or healthcare services. Conclusion/Implications In a city whose model is built upon the close monitoring of pets and their people, the issue of data linkages is critical. New partnerships and new solutions, respectful of citizen privacy and organizations’ respective scope of practice, should be developed.